The Influence of After-Sales Service, Product Quality, and Brand Resonance on Brand Loyalty with Customer Satisfaction as an Intervening Variable at PT Suzuki Indomobil Motor - Pratiwi, Nabila; Madiawati, Putu Nina; Hidayat, Agus Maolana (AGUSPATI Research Institute, 2025)
This study examines the relationship between after-sales service, product quality, and brand resonance on brand loyalty with customer satisfaction acting as a intervening variable at PT Suzuki Indomobil Motor. This study uses a non-probability sam-pling method with purposive sampling, by applying the Slovin formula to determine the sample size. Data were collected through questionnaires, resulting in a sample of 400 consumers of PT Suzuki Indomobil Motor in Jabodetabek. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that after-sales service has a significant and positive influence on customer satisfaction. Product quality also has a significant and positive influence on customer satisfaction. In addition, brand resonance also significantly and positively affects customer satisfaction. Furthermore, the results of this study show that customer satisfaction mediates the relationship between after-sales service, product quality and brand resonance among PT Suzuki Indomobil Motor customers. These findings provide valuable insights for PT Suzuki Indomobil Motor as well as other four-wheeler automotive companies, regarding the importance of creating after-sales service that meets consumer expectations, good product quality and creating and maintaining good relationships between brands and consumers.